Analysis of the system of pricing of railway capacity allocation in the Czech Republic - Široký, Jaromír; Saláková, Hana (EDP Sciences, 2018)
The introducing of legal background for capacity allocation in Czech Republic. The analysis of price for capacity allocation in Czech Republic and in Europe. The proposal of the capacity allocation price which should lead the Railway undertaking's path request to the suitable product. Possible impact of the price of capacity allocation to Railway undertaking's decision about the railway transport.
Analýza systému stanovení ceny za přidělování kapacity dráhy v ČR
Keywords: railway; capacity; allocation; railway transport.; železnice; kapacita; alokace; železniční doprava.